2021
DOI: 10.5603/dk.a2021.0010
|View full text |Cite
|
Sign up to set email alerts
|

Euglycemic diabetic ketoacidosis associated with empagliflozin in patients hospitalized with acute pulmonary embolism

Abstract: Euglycemic diabetic ketoacidosis (Eu-DKA) is a rare but life-threatening complication in diabetic patient treated with sodium-glucose cotransporter 2 inhibitors (SglT2i). A 71-year-old diabetic female treated with empagliflozin presented to the ED with shortness of breath. Diagnosis of acute pulmonary embolism was confirmed initially. She was treated conservatively with subcutaneous enoxaparin 60 mg bidaily. and oxygen therapy. respiratory distress associated with anion gap -metabolic acidosis and ketosis deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…[ 75 ] While the exact mechanism behind this is unclear, it may be due to Canagliflozin's ability to simultaneously increase glucagon secretion causing gluconeogenesis while increasing UGE, resulting in the excessive formation of ketones. [ 76 ] In addition to this, it is shown that the excessive reabsorption of ketone bodies from the kidney is likely because of the positive electrochemical gradient created when SGLT2 is inhibited. [ 77 ] Increased fractures have only been observed in the CANVAS trials, with a balanced spread of upper and lower limb fractures occurring in 4% of patients taking Canagliflozin versus 2.6% of those taking placebo.…”
Section: Introductionmentioning
confidence: 99%
“…[ 75 ] While the exact mechanism behind this is unclear, it may be due to Canagliflozin's ability to simultaneously increase glucagon secretion causing gluconeogenesis while increasing UGE, resulting in the excessive formation of ketones. [ 76 ] In addition to this, it is shown that the excessive reabsorption of ketone bodies from the kidney is likely because of the positive electrochemical gradient created when SGLT2 is inhibited. [ 77 ] Increased fractures have only been observed in the CANVAS trials, with a balanced spread of upper and lower limb fractures occurring in 4% of patients taking Canagliflozin versus 2.6% of those taking placebo.…”
Section: Introductionmentioning
confidence: 99%
“…However, the prevalence of EDKA increased after the introduction of sodium-glucose transporter 2 (SGLT2) inhibitors in some rare cases. Although there have been few reports of DKA in SGLT2i investigations, the precise numbers of EDKA events have not been evaluated (Wibawa et al, 2021). The results of another trial,"the EMPA-REG OUTCOME (Empagliflozin Cardiovascular Outcome Event Trial in Type 2 Diabetes Mellitus Patients-Removing Excess Glucose)" study, revealed that DKA occurs less frequently than 0.1% of the duration (Rosenstock, 2015;Sampani et al, 2020).…”
Section: Abbreviationsmentioning
confidence: 99%